Penyusunan Laporan Keuangan Berdasarkan Sak Etap Pada Koperasi Wanita “Usaha Bersama” - Srikalimah, Srikalimah -; Nadhiroh, Umi; Indriani, Siti Rochmah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
This research is conducted at Koperasi Wanita “Usaha Bersama”in Ngletih village, Kandat distric, Kediri. The research is to know how to make financial report at Koperasi Wanita “Usaha Bersama” in accordance with the Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP). This research used data collection tecniques with interviews and transaction documents, The method of data analysis in this study uses descriptive analysis by identifying data or document, evidences of financial transasctions and preparing financial statements in accordance SAK ETAP The results of the study indicate that Koperasi Wanita “Usaha Bersama” in presenting financial report only Income statement and Balance sheet asled to the SAK ETAP, the fact there are a few post that are not yet in accordance with SAK ETAP. So the report prepared by the researchers is the Balance Sheet, Income Statement, Statement of Changes in Equity, Cash Flow Statement and Notes to Financial Statements. Supervisors Koperasi Wanita ““Usaha Bersama” response regarding the preparation of the financial statements based SAK ETAP is less familiar because lack of knowledge of human resources and the changes of old cooperative management. It is better if the cooperative management join training which held by Dinas Koperasi to understand the components in preparing financial statements in accordance with the SAK ETAP Keywords : Financial Reports, SAK ETAP